2016
DOI: 10.1111/phn.12282
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Multiple Behavioral Risk Factors for Cancer in Rural Women

Abstract: Objectives This study examined demographic and health-related factors associated with risk behaviors that have been linked to cancer including smoking, high BMI, and low physical activity. Design and Sample A secondary analysis was conducted using data from Rural Families Speak about Health, a multi-state, epidemiologic study of rural American women and their families (N=444). Measurement Validated measures for various demographic and health related items including tobacco use, BMI, physical activity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…In addition, nurses need to discuss unmodifiable correlates with their cancer patients in order to adequately inform and educate them regarding optimal care and prevention if these patients are to maintain their health to the greatest extent possible. Especially for public health nurses who practice in rural settings where there are often fewer health providers, targeting multiple health behaviors related to cancer at once may be especially efficient in utilizing their time and resources (Noonan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nurses need to discuss unmodifiable correlates with their cancer patients in order to adequately inform and educate them regarding optimal care and prevention if these patients are to maintain their health to the greatest extent possible. Especially for public health nurses who practice in rural settings where there are often fewer health providers, targeting multiple health behaviors related to cancer at once may be especially efficient in utilizing their time and resources (Noonan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…10−12 Patients in rural areas face multiple challenges in obtaining cancer treatment, including long travel times, lack of access to specialists and clinical trials, and limited financial resources. 13,14 Previous research has found that patients with breast, cervical, endometrial, and ovarian cancer in rural areas are more likely to be diagnosed at advanced stages and less likely to receive guideline-concordant radiation, chemotherapy, and surgery. 11,15−17 Disparities in surgical access and poorer survival have been reported for patients with lung, prostate, and colorectal cancers.…”
mentioning
confidence: 99%
“…In a study conducted in a rural areas in the US., it was found the rates of obese people and people with low physical activity were higher than the rates for other combinations of cancer risk behaviors (31). Another study found that the rates in combination of tobacco and alcohol use were higher than other cancer risk behaviors (6).…”
Section: Discussionmentioning
confidence: 99%